Preservation of Mullets in CO2 Enriched O Gas-mixture at 6-7 C - Gupta, S.S.; Basu, Subrata; Panduranga Rao, C.C.; Chakraborti, R. (Fishery Technology, 2025)
Small mullets were stored at 6-7Â°C in gas mixtures containing 60% carbon dioxide & 40% air and 80% carbon dioxide & 20% air. It was found that fish stored in gas mixture containing 60% carbon dioxide and 40% air was acceptable upto 9 days and that stored in 80% carbon dioxide and 20% air upto 10 days as compared to 7 days for control packed in normal atmosphere.